OPTIMALIZATION EFFICIENCY OF PAS 99 INTEGRATED MANAGEMENT SYSTEM IMPLEMENTATION ON A STATE-OWNED ENTERPRISE IN THE TELECOMMUNICATIONS SECTOR - Muhammad Faisal Rahman; Ikasari, Diana (ZONAsi: Jurnal Sistem Informasi, 2025)
Good Corporate Governance (GCG), as regulated in PER-2/MBU/03/2023, is designed to enhance organizational performance through an efficient governance framework. The implementation of GCG has become a pivotal role in fostering stakeholder trust, ensuring accountability, and improving operational efficiency by minimizing redundancy, particularly in the repetitive application of the Plan-Do-Check-Act (PDCA) cycle cross individual management systems-making system- thereby necessitating system integration. This study evaluates the efficiency of implementing an Integrated Management System (IMS) based on ISO 20000-1:2018; ISO 22301:2019; and ISO 27001:2013 through the PAS 99 framework in a state-owned telecommunications enterprise subsidiary. Employing a qualitative method and case study approach, the research conducts a gap reductions in redundancy, improvements in operational efficiency, and enhanced organizational capability in maintaining certifications. Key success factors includes top management commitment, understanding of organizational context, and procedural alignment across standards. The study recommends leveraging PAS 99 structure more effectively and strengthening human resource capabilities to ensure the long-term sustainability and continuous improvement of the integrated system.